Science for transformative change: the IPCC, boundary work and the making of useable knowledge - Lidskog, Rolf (Frontiers in Climate, 2024)
While there has been much discussion about what kind of expertise the IPCC needs to develop to (better) guide climate policy, little has been said about how the experts themselves assess the challenges of making science policy-relevant. The paper aims to address this gap by exploring how leading IPCC experts reflect on and evaluate their work. The empirical material consists of an interview study with experts currently or recently involved in the IPCC. The selection strategy aimed to achieve a broad range of experience among those with key roles in the assessment work, including experts from all three working groups, from different regions, and of different genders. Data from the interviews was analyzed thematically using NVivo. The concept of boundary work was used to analyze the distinctions and boundaries in this work; how the IPCC experts draw boundaries between science and policy, between policy-relevance and policy-prescriptiveness, and between certain and uncertain knowledge. By analyzing the experts’ own experiences and ideas about what makes science relevant to policy-making, the paper contributes to the discussion about current and future challenges for the IPCC.